EFFECT OF PLANT SPACINGS ON GROWTH YIELD AND LINT QUALITY OF FIVE COTTON CULTIVARS - & Askar, Al-Naqeeb (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A Field experiment was conducted at the experimental field ,Department of field Crop ,College of Agriculture /University of Baghdad during summer season 2014.In order to study the effect of plant spacings on growth yield and lint qualities. The study included two factors, the first was varieties (Coker 310 , Marsum 1, Lashata , Ashur and Abu Ghraib 5 ) as whole plots , The second factor was spacing between plants with three level (20 , 25 and 30) cm as sub plots, Using complete randomized block design under split plots with four replications. The results showed significant differences between varieties in most studied characteristic. Coker 310 gave highest average for seed cotton yield and lint cotton yield, 1457.00 and 439.13 kg ha-1 due to gave highest average in number of open bolls 8.93 boll plant-1as well as gave best average of lint length 27.98 mm, lint strength 21.54 gm tex-1. Ashur var. gave lowest average of seed cotton yield and lint cotton yield, 1120.32 and 370.64 kg ha-1 respectively, lint length 27.40 mm, Micronaire 3.29 and lint strength 19.68 gm tex-1. The Abu –Ghraibs var. gave best average after Coker 310 var. for all characterise comparing with the other varieties. It was superior of seed cotton yield and lint yield. Varieties planted on 20 cm distance between hill gave significantly superior in the average boll weight, 3.63 gm ,seed cotton yield, 1364.85 kg ha-1 ,lint yield, 432.13 kg ha-1, While The varieties plants on 30 cm distance was significantly superior in plant height, 146.15 cm, Sympodial number(15.21) plant-1, and number of open boll ( 8.99 boll plant-1).It can be recommended to cultivate coker310 with 30 cm distance to get the best result.